An architectural exfoliated-graphene carbon aerogel with superhydrophobicity and efficient selectivity - Yutong Lu; Huiqing Wang; Yun Lu (Materials & Design, 2019)
In the study, in order to completely utilize the advantages of graphene monolayer, nano-fibrillated cellulose with cations from polyethyleneimine (PEI) was used as the intercalator to efficiently exfoliate the reduced graphene oxide into a single layer with a thickness about 0.47 nm by means of ionic attraction. After the high-temperature treatment (800 °C), the carbon aerogel (NC-GO@NFC) with an architectural structure was manufactured by combining 2D monolayer graphene with 1D nano-fibrillated cellulose. The pore volume (0.55 cm3/g) and specific surface area (441 m2/g) of NC-GO@NFC were about two times higher than those of GO carbon aerogel. Particularly, the buoyant porous aerogel showed superhydrophobicity with a large water contact angle (155.5°) due to the increase of -NH- and CC as well as the pyrolysis of hydrophilic groups. The superhydrophobicity endows the aerogel with an exceptional oil/water separation performance. The carbon aerogels exhibited the adsorption capability towards many organic phases (including lubricating oil and some organic solvents). In addition, the efficient continuous removal and collection of organic solvents (methylbenzene) from water surface was achieved by a designed water/oil pump device. Therefore, the recyclable 3D porous composite aerogel had the application potential as organic solvent adsorbents and oil/water separation agents. Keywords: Exfoliated graphene, Superhydrophobic, Sorbent, Carbonization, Nano-fibrillated cellulose, Graphene